2014
DOI: 10.3390/ijms15046009
|View full text |Cite
|
Sign up to set email alerts
|

The Hydraulic Mechanism of the Unfolding of Hind Wings in Dorcus titanus platymelus (Order: Coleoptera)

Abstract: In most beetles, the hind wings are thin and fragile; when at rest, they are held over the back of the beetle. When the hind wing unfolds, it provides the necessary aerodynamic forces for flight. In this paper, we investigate the hydraulic mechanism of the unfolding process of the hind wings in Dorcus titanus platymelus (Oder: Coleoptera). The wing unfolding process of Dorcus titanus platymelus was examined using high speed camera sequences (400 frames/s), and the hydraulic pressure in the veins was measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 21 publications
3
34
2
Order By: Relevance
“…1 . The exocuticle, endocuticle, and epidermis layers appear brown and light pink (the thin basement membrane), respectively, in a manner similar to that found in [20]. It was shown that vein cavities are irregularly shaped, and their cross-section cavities get smaller and smaller.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…1 . The exocuticle, endocuticle, and epidermis layers appear brown and light pink (the thin basement membrane), respectively, in a manner similar to that found in [20]. It was shown that vein cavities are irregularly shaped, and their cross-section cavities get smaller and smaller.…”
Section: Resultssupporting
confidence: 71%
“…Microstructure testing was conducted in a manner similar to that described in [20]. The microstructures of the cross sections of hind wing veins were captured using an inverted fluorescence microscope (OLYMPUS, LX71).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have found that the intrinsic elasticity acting in wing veins allows this high-speed wing deployment (1)(2)(3)(4)(5)(6). Investigation in other species of beetles indicated the existence of a hydraulic mechanism that straightens the wing veins (7). In contrast, the other fundamental problem, namely, the mechanism behind the folding of these wings, remains unclear.…”
mentioning
confidence: 99%